Tackle the Problem When It Gets Here: Pandemic Preparedness Among Small and Medium Businesses - Watkins, Rochelle; Cooke, Feonagh; Donovan, Robert; MacIntyre, C.; Itzwerth, R.; Plant, Aileen (Sage Publications, 2008)
Globally, governments and health authorities are preparing for pandemic influenza and producing resources to promote preparedness planning; however, there is little information available to inform the design of strategies to promote preparedness. Three focus groups were conducted to identify and to describe beliefs and perceptions about pandemic influenza and response planning among small and medium business owners and managers. Most participants were not concerned about the risk of pandemic influenza, and none had engaged in any planning for a pandemic. Findings show that participants were uncertain of the modes of transmission of pandemic influenza and what precautions could be taken prior to, or in the event of, a pandemic. Among the most important findings was participants' perceived inability to effectively prevent or control the spread of influenza within their workplace. These findings have important implications for the design of communication strategies to promote preparedness.